2017
DOI: 10.1039/c7dt01562c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction intermediates in the heme degradation reaction by HutZ from Vibrio cholerae

Abstract: HutZ is a heme-degrading enzyme in Vibrio cholerae. It converts heme to biliverdin via verdoheme, suggesting that it follows the same reaction mechanism as that of mammalian heme oxygenase. However, none of the key intermediates have been identified. In this study, we applied steady-state and time-resolved UV-vis absorption and resonance Raman spectroscopy to study the reaction of heme-HutZ complex with H2O2 or ascorbic acid. We characterized three intermediates: oxyferrous heme, meso-hydroxyheme, and verdohem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…7. For all Arg92 mutants, absorption of the Soret band decreased rapidly with an increase in absorption at 645-648 nm, suggestive of verdoheme formation [33], as observed at pH 8.0 ( Fig. 5).…”
Section: Heme Degradation Activity Of Heme-arg92 Mutants At Ph 60supporting
confidence: 53%
See 1 more Smart Citation
“…7. For all Arg92 mutants, absorption of the Soret band decreased rapidly with an increase in absorption at 645-648 nm, suggestive of verdoheme formation [33], as observed at pH 8.0 ( Fig. 5).…”
Section: Heme Degradation Activity Of Heme-arg92 Mutants At Ph 60supporting
confidence: 53%
“…Arg92 appeared necessary for heme degradation when ascorbic acid was used as the electron donor, since almost no iron was released from heme after reaction with ascorbic acid. Considering that the mutants converted heme to verdoheme in the reaction with hydrogen peroxide (H 2 O 2 ), Arg92 may play a key role in transferring H + to a heme degradation intermediate, Fe 3+ -OO -, presumed to be a rate-limiting step of heme degradation by HutZ [33]. In contrast to hHO, HutZ is a dimeric protein.…”
Section: Introductionmentioning
confidence: 99%
“…We further recently succeeded in obtaining the Fe--O 2 stretching mode (ν Fe--O2 ) for heme--HutZ using a rapid mixing technique combined with resonance Raman spectroscopy. 26 The frequency of ν Fe--O2 for oxyferrous heme--HutZ was 565 cm -1 -significantly lower than that for P450 and nitric oxide synthase with Cys as a heme axial ligand (~520 cm -1 ), 38,39 but close to that for proteins with His as a heme axial ligand (~565 cm -1 for hemoglobin). 40,41 The fact that ν Fe--O2 for oxyferrous heme--HutZ was almost the same as that for HO 42 indicated that electron donation from the proximal His of HutZ was at the same level as that of HO, but not as strong as P450 or nitric oxide synthase.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 86%
“…The Soret band diminished immediately after the addition of H 2 O 2 with a concomitant increase in a band at 644 nm, indicating the formation of verdoheme, as was the case for heme--WT HutZ. Although the band at 644 nm, which is derived from verdoheme, 26 appeared, the absorbance at 644 nm in the reaction of the heme--A31V mutant with H 2 O 2 was approximately 70% of that of heme--WT (Fig. 9C).…”
Section: Ph-dependent Conformational Change Of the A31v Mutantmentioning
confidence: 87%
See 1 more Smart Citation